Evaulation of Antioxidant Activity of Grewia asiatica Berry Using 2,2'-Azinobis- (3-ethylbenzothiazoline-6-sulphonic acid) and N,N-Dimethyl-p-phenylenediamine Radical Cations Decolourization Assays - Nadeem Asghar, Muhammad; Ullah Khan, Islam; Sherin, Lubna; Ashfaq, Muhammad (Asian Journal of Chemistry, 2010)
Antioxidant activity and phenolic contents of fresh and stored samples of seed, peel and pulp of Grewia asiatica, a black berry, was evaluated using 2,2'-azinobis-(3-ethylbenzothiazoline-6- sulphonic acid) (ABTS) and modified N,N-dimethyl-p-phenylenediamine (DMPD) decolourization assays. Results showed that when G. asiatica is stored at 0 ºC for duration of one month, the polyphenols are partly degraded and/or transformed into other products. 2-(6- Hydroxy-2,5,7,8-tetramethylchroman-2-yl)ethanoic acid (Trolox) equivalent antioxidant capacity (TEAC) values showed that polyphenols in fresh G. asiatica samples have a potent in vitro antioxidant activity which may be related to its medicinal properties against diseases like diabetes mellitus, hepatitis, etc. The highest values of antioxidant activity were obtained for peel followed by pulp and seeds. Extraction solvents of different polarity were employed in a bid to extract maximum phenolic contents. Total phenolic contents for peel, pulp and seed were estimated spectrophotometrically using Folin-Ciocalteu reagent with gallic acid as standard. Statistically positive correlation was found between phenolic content and antioxidant activity.